All printed soft actuators based on ionic liquid/polymer hybrid materials - Correia, D. M. (2021)
Soft actuators are increasingly being required for a variety of application ranging from robotics to biomedicine. This work reports on the development of printable materials for soft actuator applications based on ionic liquids (ILs) and a fluorinated polymer, poly(vinylidene fluoride) (PVDF). ILs sharing the same cation 1‑butyl‑3-methylimidazolium, [Bmim]+ and different anions (tricyanomethanide, [C(CN3)]−, dicyanamide, [N(CN2)]− and thiocyanate, [SCN]−) were incorporated into the PVDF polymer matrix at 40% wt. and processed by direct writing printing technique. Rheological measurements of the IL/PVDF solutions allowed to stablish a correlation between shear stress and viscosity, being observed a shear thinning behavior. Independently of the IL anion, the inclusion ILs leads to variations in the sample morphology related to the formation of significantly smaller spherulites than in PVDF with well-defined borders and an increase of the electroactive β phase content and crystallinity degree of the polymer. The incorporation of the ILs into the PVDF matrix induces a mechanical plasticizing effect. A maximum ionic conductivity of 5.2 × 10−5 S/cm has been achieved for the [Bmim][N(CN2)]/PVDF composite. The potential of the developed printable materials as soft actuators has been experimentally demonstrated and theoretically evaluated, the highest displacement of 1.0 mm at an applied voltage of 4 Vpp being obtained for [Bmim][SCN]/PVDF. Finally, the implementation of an all printed micro gripper shows the potential of the materials for applications.